SOME PROBLEMS OF QUALITY ASSURANCE OF MATHEMATICAL EDUCATION OF FUTURE PRIMARY SCHOOL TEACHERS - Granichina, Olga; Sheremetyeva, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the most significant problems of ensuring the quality of mathematical education of students studying in the direction of Pedagogical Education, profile "Primary Education". The presented results were obtained as a result of the analysis of theoretical studies published in Russian scientific sources, and on the basis of a survey of mathematics teachers and methods of teaching mathematics working in leading pedagogical universities of Russia. As a result of processing the obtained data, the identified problems are ranked by degree of relevance. In the article, the authors proposed possible solutions to the identified problems within the existing regulatory requirements on the basis of their personal experience in teaching mathematical disciplines at a teacher training university, as well as possible risks that arise when they are implemented. The authors present individual examples of the implementation of these ideas in the practice of teaching students at the Herzen State Pedagogical University of Russia.